USING KWL (KNOW, WANT TO KNOW, LEARNED) STRATEGY IN TEACHING READING ANALYTICAL EXPOSITION TEXTS TO THE ELEVENTH GRADE OF MA MIFTAHUL ULUM GRESIK - Frederich Jovan Leonardo; Faishol Hadi (STKIP AL HIKMAH SURABAYA, 2026)
This study aimed to describe the implementation of the KWL (Know, Want to Know, Learned) strategy in teaching reading comprehension of analytical exposition texts and to investigate students’ responses toward its use. The study employed a descriptive qualitative method involving the eleventh-grade students of MA Miftahul Ulum Gresik as the research subjects. Data were collected through questionnaires and classroom observation. The findings revealed that the KWL strategy was implemented effectively through three stages: activating students’ prior knowledge, guiding students to formulate questions, and encouraging reflection after reading. The use of relevant analytical exposition text topics helped increase students’ engagement and comprehension. The questionnaire results indicated that most students responded positively to the KWL strategy, showing improved understanding, motivation, and participation in reading activities. Based on the findings, it can be concluded that the KWL strategy is an effective and student-centered approach for teaching reading comprehension of analytical exposition texts in EFL classrooms.